Criminalizing Aggression: How the Future of the Law on the Use of Force Rests in the Hands of the ICC. (9th November 2018) - Ruys, Tom
Abstract: The activation of Articles 8bis, 15bis and 15ter of the Rome Statute in July 2018 has once again fuelled debates over the prosecution of the crime of aggression. While various flaws and imperfections of the Kampala Amendments have attracted scholarly attention in recent years, the present article focuses on one particular source for concern – that is, the implications that the activation of the International Criminal Court's (ICC) jurisdiction may have for the legal regime governing the use of force between states. It is assumed at the outset that, even if investigations into alleged crimes of aggression may not occur on a frequent basis, sooner or later the ICC will inevitably be called upon to apply Article 8bis of the Rome Statute. Indeed, even if the majority of situations dealt with by the Court pertain to non-international armed conflicts, there have also been a number of situations involving an international/interstate element. In essence, each such situation potentially raises jus contra bellum concerns and may accordingly lead to allegations that the crime of aggression has been committed. Even if the lion's share of these allegations is unlikely to make it past the preliminary examination or investigation phases, the way in which the ICC prosecutor and the Pre-Trial Chambers play their role as gatekeepers with regard to the crime of aggression is bound to have strong repercussions for the interpretation and compliance pull of the law on the use of force. This article first addresses the possible impact of the ICC's jurisdiction over the crime of aggression on the recourse to, and acceptance of, unilateral humanitarian intervention, before addressing other ways in which it may influence the international legal framework governing the use of force.